Internal Culture Challenges And Agile Manifesto Limitations Of Agile Project Management: A Systematic Literature Review - Wijaya, Fadhil; Raharjo, Teguh (Syntax Corporation, 2022)
The adoption of agile development approaches has significantly increased. Organizations use agile approaches to accelerate software delivery and enhance ability to manage changing priorities. In fact, agile projects experience delays, over budget, customer dissatisfaction for information system projects. Previous research and survey have shown that this problem is related to internal culture and the agile manifesto value itself. This research aims to identify the challenges and limitations of agile projects based on internal culture and agile manifesto perspective. A systematic literature review technique was conducted and obtained fifteen relevant papers. This research use cause-effect relationship analysis to find the root causes of each category. There are five internal culture challenges that are generally related to incompatibility and misalignment of the current organization culture with agile approaches. There are five agile manifesto limitations that are generally related to time constraints due to short iteration cycles that lead insufficient planning and documentation in agile project management. Organization is expected to be able to correctly identify what kind of challenges category the organization is currently experiencing for determining solutions to increase project success.